The dark side of sexism in Argentina: Psychometric properties of the Short Dark Triad Personality measure and its relation with ambivalent sexism - Bria, Paula; Etchezahar, Edgardo; Ungaretti, Joaquín; Gómez Yepes, Talía (Frontiers in Psychology, 2022)
One of the main evaluation instruments of the dark side of personality has been the Short Dark Triad of Personality (SD3), that includes Machiavellianism, Narcissism and Psychopathy traits. Although other adaptations of this scale have been made in several countries, its psychometric properties have never been tested in Argentina. Different studies addressed that dark triad scores are related to different expressions of sexist prejudice. One of the issues that have been traditionally considered to understand intimate, yet unequal relationships between men and women, is prejudice toward women. Ambivalent sexism combines two types of sexist attitudes: hostile, and benevolent sexism. While hostile sexism involves attitudes of outright intolerance towards women, benevolent sexism is defined as a set of attitudes that comprises the perception of women in a positive emotional tone. The aim of the study was to analyze the Dark Triad of Personality scale in the Argentinian context and its relationships whit ambivalent sexism. A total of 1198 individuals residing in different regions of Argentina participated, from different genders (woman = 59,5%), from 18 to 75 years old (M = 45.17 SD = 15.08). Main results indicated adequate psychometric properties for the Short Dark Triad of Personality scale in the Argentinian context. In addition, the three traits of the dark triad were significantly related to hostile and benevolent sexism, which indicate that one of the variables to keep addressing in order to comprise and eventually reduce prejudice towards women would be the dark triad of personality. Main results are discussed, in order to strengthen the understanding of the relationships between the dark triad and ambivalent sexism.